Low Velocity Zones in the Martian Upper Mantle Highlighted by Sound Velocity Measurements. Issue 19 (6th October 2021) - Xu, F.; Siersch, N. C.; Gréaux, S.; Rivoldini, A.; Kuwahara, H.; Kondo, N.; Wehr, N.; Menguy, N.; Kono, Y.; Higo, Y.; Plesa, A.‐C.; Badro, J.; et al.
Abstract: The InSight mission to Mars is currently monitoring the seismic activity of the planet. Interpretation of seismological observations in terms of composition and mineralogy requires the knowledge of density and thermo‐elastic properties of constituent materials at pertinent conditions. We thus performed phase equilibria experiments and carried out sound velocity and density measurements on aggregates representative of the Martian mantle over pressures and temperatures directly relevant for Mars' upper and mid mantle. Our results indicate the stability of magnetite, although in a small amount, in phase assemblages at upper mantle conditions, especially in an oxidized environment. The measured pressure and temperature derivatives of compressional and shear velocities show that the temperature‐induced reduction of seismic wave speeds dominates over pressure‐induced effects at Mars' shallow mantle conditions for the predicted areotherms and, independently from mineralogy, support the presence of a low‐shear‐wave‐velocity layer between 150 and 350 km depth, in agreement with seismic observations. Plain Language Summary: The InSight mission operating on Mars is currently monitoring the planet's seismic activity. The recorded marsquakes can be used to obtain information on Mars' internal composition. However, the interpretation of these observations requires knowledge of the physical properties of the minerals expected to compose the Martian mantle at the relevant conditions. In this study we report: (1) experiments investigating the nature and abundance of the mineral phases stable at Martian mantle conditions; (2) sound velocity and density measurements on these rocks over a pressure and temperature range directly relevant for Mars' mantle, providing information that can be directly compared to the seismological findings from the InSight mission. Our results reveal the stability of small amounts of magnetite, an Fe 3+ ‐rich mineral not reported in previous studies but a likely candidate in Mars' oxidized mantle environment. Moreover, measured wave velocities indicate the existence of a region between 150 and 350 km depth where, due to large temperature‐induced reduction, shear wave velocities decrease with depth as opposed to an expected increase. This finding is consistent with recent observations from the InSight mission on Mars. Key Points: Sound wave velocities and density were measured for pressures, temperatures, and mineralogical assemblages representative of Mars' mantle Experimental results support the existence of a low shear velocity layer in the shallow Martian mantle Phase equilibria experiments suggest the existence of ferrian minerals in the oxidized regions of the uppermost Martian mantle